Palliative Intensity Modulated Radiation Therapy for Symptomatic Adrenal Metastasis - Patel V, Mod H (Journal of Nepal Health Research Council, 2013)
Metastasis to the adrenal glands is quite common; especially from melanomas, breast, lung, renal and gastro-intestinal tumours. The most common tumour found in the adrenals in post mortem series is a metastatic tumour; incidence ranging from 13 to 27%. The diagnosis of adrenal metastasis is now more common and easier due to staging and subsequent follow up with Computed tomography /Magnetic resonance imaging and or positron emission tomography-computed tomography imaging studies. Most of the times these metastatic lesions are clinically occult and those that do have clinical symptoms complain of pain, nausea, vomiting and early satiety. We irradiated a patient of non small cell lung cancer with adrenal metastasis with palliative Intensity Modulated Radiation Therapy and achieved a good response in terms of pain relief, stable disease and no side effects of the treatment